Renewable Energy in Marine Environment - Rusu, Eugen (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The effects of human-caused global warming are obvious, requiring new strategies and approaches. The concept of business-as-usual is now no longer beneficial. Extraction of renewable energy in marine environments represents a viable solution and an important path for the future. These huge renewable energy resources in seas and oceans can be harvested, including wind, tide, and waves. Despite the initial difficulties related mostly to the elevated operational risks in the harsh marine environment, newly developed technologies are economically effective or promising. Simultaneously, many challenges remain to be faced. These are the main issues targeted by the present book, which is associated with the Special Issue of Energies Journal entitled "Renewable Energy in Marine Environment". Papers on innovative technical developments, reviews, case studies, and analytics, as well as assessments, and papers from different disciplines that are relevant to the topic are included. From this perspective, we hope that the results presented are of interest to for scientists and those in related fields such as energy and marine environments, as well as for a wider audience.